'You're in this world now': Students', teachers', and parents' experiences of school transition and how they feel it can be improved. (13th March 2019) - Bagnall, Charlotte Louise; Skipper, Yvonne; Fox, Claire Louise
Abstract : Background: Primary–secondary school transition is a major life event for 11‐year‐old children in the United Kingdom and can also be a stressful period for parents and teachers. However, most research focuses on the impact of transition on children's academic performance and social well‐being and we have a limited understanding of their emotional experiences in the lead up to and during the transition, from the perspective of key stakeholders: students, parents, and teachers. Aims: To explore transfer students', parents', and teachers' experiences in the lead up to and over the transition period, and how they feel it could be improved. Sample: The sample consisted of 45 year seven students, 8 year seven parents, 8 year seven teachers, and 8 year six teachers, recruited from five primary and five secondary schools. Method: Students participated in face‐to‐face semi‐structured focus groups and adults in asynchronous online focus groups. Transcribed audio‐recordings were analysed using inductive thematic analysis. Results: Students, parents, and teachers were shown to navigate a similar process over primary–secondary school transition. All talked about managing their own and others' emotions, relationships, and expectations. These were shaped by shared communication across primary and secondary schools and between the stakeholders, and impacted by how good transition provision was seen to be. Conclusions: There is a need to understand the transition period from the perspective of students, teachers, and parents, to improve school transition. This information will allow us to design emotional centred support interventions that reflect these lived experiences.